Towards an integrated approach to postcolonial and non‐postcolonial Englishes - BUSCHFELD, SARAH; KAUTZSCH, ALEXANDER (World Englishes, 2017)
ABSTRACT The categories ‘ESL’ and ‘EFL’ should not be seen as discrete as traditionally assumed but as located on a continuum. Since the traditional categorization as either foreign or second‐language English strongly depends on the historical and sociopolitical development of a territory, with postcolonial speech communities normally ascribed ESL status and non‐postcolonial speech communities being treated as EFL, recent research has made first attempts for an integrative analysis of such Englishes. Based on the framework of Schneider's Dynamic Model, the paper at hand introduces the model of Extra‐ and Intra‐territorial Forces (EIF model) to meet the aim of a joint approach to those Englishes which have so far mostly been treated independently of each other. Its practical application is demonstrated in reference to the development of English in Namibia.